The long haul - Kinney, Jeff (New York : Amulet Books, 2014)
Greg Heffley and his family hit the streets for a wimpy kid-style road trip.
Keywords: Automobile travel -- Juvenile fiction; Families -- Juvenile fiction; Diaries -- Juvenile fiction; Humorous stories